Foreign Language Anxiety and Academic Achievement: Is There Any Relationship in Between? - Azzahra, Zulfa Ghefira; Fatimah, Fatimah (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2023)
Psychological factors can contribute to the devitalization or acceleration of foreign language learning. Foreign Language Anxiety (FLA) is widely discussed in various studies, namely on Second Language Acquisition (SLA). This research aims to explore one of the psychological effects of learning a foreign language, specifically Foreign Language Anxiety (FLA), and its effect and correlation on academic achievement. 43 undergraduate students from the Department of English were chosen as the participants of the study. To conduct the findings, this study adopts a quantitative approach with descriptive analysis and Pearson correlation. The findings of the study presented that the students encounter a moderately low level of foreign language anxiety (M = 2.75, SD = .86). The findings also reveal that the relationship between the students’ foreign language anxiety level and academic achievement shows no correlation between one another (r = -0.9). The implication of this study is that language teachers should continuously encourage students to be more self-assured in their second language learning as well as alleviate their language anxiety level.